Solution: Solve xy’ (2y-1)=y(1-x)

(Last Updated On: January 22, 2020)

Solve xy’ (2y – 1) = y (1 – x)

Problem Statement: EE Board April 1996

Solve xy’ (2y-1)=y(1-x)

  • A. ln (xy) = 2 (x – y) + C
  • B. ln (xy) = x – 2y + C
  • C. ln (xy) = 2y – x + C
  • D. ln (xy) = x + 2y + C

Problem Answer:

The solution is ln (xy) = x + 2y + C

View Solution:
Solution: Solve xy’ (2y-1)=y(1-x)

Latest Problem Solving in Differential Equations

More Questions in: Differential Equations

Online Questions and Answers in Differential Equations

Print Friendly, PDF & Email
Please do Subscribe on YouTube!

P inoyBIX educates thousands of reviewers and students a day in preparation for their board examinations. Also provides professionals with materials for their lectures and practice exams. Help me go forward with the same spirit.

“Will you subscribe today via YOUTUBE?”


Add Comment

PinoyBIX Engineering. © 2014-2021 All Rights Reserved | How to Donate? | Follow me on Blogarama Protection Status